Histoire de l'Outaouais - Gossage, Peter (Labour / Le Travail, 1995)
The article reviews the book, "Histoire de l'Outaouais," by Chad Gaffield, André Cellard, Gérald Pelletier, Odette Vincent-Domey, Caroline Andrew, André Beaucage, Normand Fortier, Jean Harvey, and Jean-Marc Soucy.
Keywords: ANDREW; Caroline; BEAUCAGE; Andre; BOOKS – Reviews; CELLARD; Andre; FORTIER; Normand; GAFFIELD; Chad; 1951-; HARVEY; Jean; HISTOIRE de l'Outaouais (Book); Nonfiction; PELLETIER; Gerald; PHYSICAL geography; SOUCY; Jean-Marc; VINCENT-Domey; Odette